2018
DOI: 10.1159/000490230
|View full text |Cite
|
Sign up to set email alerts
|

Significance of High-Risk Human Papillomavirus Testing for Atypical Glandular Cells on Cervical Cytology

Abstract: Objectives: The aim of this study was to evaluate the diagnostic significance of high-risk human papillomavirus (hrHPV) testing for managing women with atypical glandular cells (AGC) and to explore the distribution of hrHPV genotypes. Methods: We analyzed cytologic and histopathologic diagnoses in patients referred to our institution due to AGC or atypical squamous cells of undetermined significance (ASC-US). All patients underwent hrHPV testing and genotyping, and positive (PPV) and negative predictive values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The sizeable CIN 3 or worse risk we found for all different groups of HPV types support this recommendation. Nevertheless, as other studies have also shown, the risk for cervical precancer and invasive cancer associated with HPV positivity 4–6 and different HPV types 7,21–24 might be useful for the management of AGC. Risk stratification by HPV types might also be helpful to assist prioritization of women for follow-up when resources and referral capacity are limited.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The sizeable CIN 3 or worse risk we found for all different groups of HPV types support this recommendation. Nevertheless, as other studies have also shown, the risk for cervical precancer and invasive cancer associated with HPV positivity 4–6 and different HPV types 7,21–24 might be useful for the management of AGC. Risk stratification by HPV types might also be helpful to assist prioritization of women for follow-up when resources and referral capacity are limited.…”
Section: Discussionmentioning
confidence: 92%
“…A study from Korea found that HPV genotypes 51/52/53/56/58/59 combined were the most frequent types after HPV16/18 among 90 high-risk HPV-positive AGC cases. 22 From their study in Japan, Komatsu et al 23 Namugenyi et al 24 found HPV45 and 68 to be most common high-risk HPV types after HPV16 among 18 high-risk-positive women with AGC. A multiinstitutional retrospective study by Bogani and colleagues 25 from Italy found HPV58 and HPV31 to be the most common types after HPV16/18 among 136 AGC cases with positive HPV DNA testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations for practice based on our findings and the current literature would be to consider HR HPV plus BNC in endocervical cells a high‐grade referral (ie, to be assessed in colposcopy within 2 weeks of the referral) and efforts should be made not to rebook these women. Due to the low incidence of this cytological finding, this should not have a significant impact upon the workload of a colposcopy department.…”
Section: Discussionmentioning
confidence: 99%